Cover Picture: The Sex Attractant Pheromone of Male Brown Rats: Identification and Field Experiment (Angew. Chem. Int. Ed. 20/2016). Issue 20 (10th May 2016) - Takács, Stephen; Gries, Regine; Zhai, Huimin; Gries, Gerhard
Abstract : The male brown rat marks his territory with urine deposits, thereby deterring potential male intruders while retaining females within his deme and attracting wandering females to it. In their Communication onpage 6062 ff., G. Gries et al. report the identification and field testing of the urine‐derived sex pheromone, which, when added to food‐baited traps, increases the capture of wild female rats by a factor of ten. The pheromone could improve the efficacy of rat control tactics (picture: S. McCann and S. DeMuth).